Modelos para predizer exigências protéicas para codornas de corte - Ferreira, Mariana Fátima Zanon (2014)
Four experiments were carried out in order to determine the protein requirements for maintenance (CPm) and weight gain (CPg) of meat quails, develop prediction equations of crude protein requirements and evaluate their applications. In experiment 1, in order to determine the CPm requirement using the technique of nitrogen balance, 80 meat quails were used, with 24 days of age, housed in metabolism cages and distributed in a completely randomized design with four treatments and five replicates of four birds each. The treatments consisted of diets with increasing levels of CP: 4; 10.5; 17 and 23.5%. Total excreta collection and quantification of feed intake were performed. Through regression of nitrogen balance in relation to nitrogen intake the CPm requirement of 2.94 g/kg0.75/day was obtained. In experiment 2, in order to determine the requirement of CPm by the comparative slaughter technique, 600 meat quails were used, with 15 days of age, distributed in a completely randomized design, with four treatments and five replicates of 30 birds each. The treatments consisted in a basal diet with ad libitum consumption, 70, 50 and 30% ad libitum, with the feed intake quantified daily. Referential slaughters were performed at 15 and 35 days of age. The retained (RN) and ingested (IN) nitrogen were quantified considering the metabolic weight of the birds. Through linear regression between the RN in the carcasses in relation to IN the requirement of CPm in 7.88 g/kg0.75/ day was estimated. Experiment 3 aimed to determine the requirements of CPg. 280 meat quails were used on day zero, housed in five experimental units, totaling 56 birds each, and fed with basal diets ad libitum. Weekly slaughters were performed and through regression of the body nitrogen of carcasses in relation to body weight in fasting, the requirements of CPg were estimated: 439.19 (0 to7 days); 540.54 (8 to 14 days); 506.76 (0 to 14 days); 557.43 (15 to 21 days); 675.68 (22 to 28 days); 456.08 (29 to 35 days) and 557.43 mg/g (15 to 35 days). In experiment 4, in order to evaluate models for prediction of crude protein requirements, 250 meat quails were used, on day zero, housed in five boxes, totaling 50 birds each and fed with basal diets formulated to meet the nutritional requirements of the quails. The weight gain (WG), body weight (BW) and feed intake (FI) were calculated weekly. The prediction models were elaborated considering the coefficients of protein requirements for maintenance (CPm), obtained by the techniques of nitrogen balance (NB) and comparative slaughter (CS), and the protein requirements for weight gain determined in the experiments 1, 2 and 3. The data of daily WG and BW were applied to models to determine the estimated intakes of CP, which were compared with observed intakes of CP. The comparison of the results was performed by calculating the differences and the sum of squares of differences. The models evaluated using the requirement of CPm determined by NB technique showed the best adjustment to the observed intakes of CP. Considering the CPm requirement determined by NB, the models of protein requirements elaborated for meat quails were: CP= 2.94W0.75 + 0.439G (0 to 7 days); CP= 2.94W0.75 + 0.541G (8 to 14 days); CP= 2.94W0.75 + 0.507G (0 to 14 days); CP= 2.94W0.75 + 0.557G (15 to 21 days); CP= 2.94W0.75 + 0.676G (22 to 28 days); CP= 2.94W0.75 + 0.456G (29 to 35 days); CP= 2.94W0.75 + 0.557G (15 to 35 days). These models presented a good prediction of protein requirements for meat quails, and thus can be used by companies, producers and nutritionists.